Developing antimicrobial medicinal plants pocketbook based on local wisdom of Muko-Muko and Serawai ethnics - Alif Yanuar Zukmadini; Dewi Jumiarni; Kasrina Kasrina (JPBI (Jurnal Pendidikan Biologi Indonesia), 2018)
The using of teaching materials based on local wisdom is still limited. This study aimed to develop a pocketbook based on research results of antimicrobial medicinal plants from Muko-muko and Serawai ethnics as supplementary teaching materials for senior high school students. This study was Research and Development (R&D) model by Sugiyono that consisted of five stages, namely: potential and problems analysis, data collection, product design, design validation, and design correction. The designed pocketbook was validated by learning source expert and material expert. The data obtained  were analyzed using statistical descriptive (percentage). The validation data score from learning source expert was 93.4% and material expert was 98.86% which were recognized as ‘very good’. Thus the developed pocketbook is valid as a supplementary teaching materials in biology learning for senior high school.